Mapping properties for convolution involving hypergeometric series - Aouf, M. K.; Mostafa, A. O.; Zayed, H. M. (Ukrains’kyi Matematychnyi Zhurnal, 2018)
We introduce sufficient conditions of (Gaussian) hypergeometric functions to be in a subclass of analytic functions. In addition, we investigate several mapping properties for convolution and integral convolution involving hypergeometric functions.